Association of Anagrus amazonensis Triapitsyn, Querino & Feitosa (Hymenoptera, Mymaridae) with aquatic insects in upland streams and floodplain lakes in central Amazonia, Brazil - Feitosa, Malu Christine Barbosa; Querino, Ranyse Barbosa; Hamada, Neusa (Revista Brasileira de Entomologia, 2016)
Anagrus amazonensis Triapitsyn, Querino & Feitosa (Hymenoptera, Mymaridae) is a parasitoid that uses aquatic insect eggs as a host for the development of its immature stages. The objectives of this study are to record the interaction between A. amazonensis and its hosts and the aquatic plants used by these hosts to lay their eggs. Field work was conducted in floodplain lakes and upland (terra firme) streams, in four municipalities in Amazonas State, Brazil, where aquatic plants were scanned for the presence of aquatic insect eggs. In the laboratory, eggs were maintained in plastic containers with water until the emergence of the parasitoid or of the first instar insect. A total of 1223 adults of A. amazonensis emerged from eggs of Hemiptera, Lepidoptera and Odonata; these eggs were collected on 12 species of aquatic plants. © 2016 Sociedade Brasileira de Entomologia